Suaahara in Nepal: An at‐scale, multi‐sectoral nutrition program influences knowledge and practices while enhancing equity. Issue 4 (6th January 2017) - Cunningham, Kenda; Singh, Akriti; Pandey Rana, Pooja; Brye, Laura; Alayon, Silvia; Lapping, Karin; Gautam, Bindu; Underwood, Carol; Klemm, Rolf D. W.
Abstract: The burden of undernutrition in South Asia is greater than anywhere else. Policies and programmatic efforts increasingly address health and non‐health determinants of undernutrition. In Nepal, one large‐scale integrated nutrition program, Suaahara, aimed to reduce undernutrition among women and children in the 1, 000‐day period, while simultaneously addressing inequities. In this study, we use household‐level process evaluation data ( N = 480) to assess levels of exposure to program inputs and levels of knowledge and practices related to health, nutrition, and water, sanitation, and hygiene (WASH). We also assess Suaahara's effect on the differences between disadvantaged (DAG) and non‐disadvantaged households in exposure, knowledge, and practice indicators. All regression models were adjusted for potential confounders at the child‐, maternal‐, and household levels, as well as clustering. We found a higher prevalence of almost all exposure and knowledge indicators and some practice indicators in Suaahara areas versus comparison areas. A higher proportion of DAG households in Suaahara areas reported exposure, were knowledgeable, and practiced optimal behaviors related to nearly all maternal and child health, nutrition, and WASH indicators than DAG households in non‐ Suaahara areas and sometimes even than non‐DAG households in Suaahara areas. Moreover, differences in some of these indicators between DAG and non‐DAG households were significantly smaller in Suaahara areas than in comparison areas. These results indicate that large‐scale integrated interventions can influence nutrition‐related knowledge and practices, while simultaneously reducing inequities.